Preparation method and application of recoverable Fe2O3 / NiOx nano-enzyme

The Fe2O3/NiOx nanoenzyme prepared by the melt salt preparation method is magnetic and can be recovered through magnetic properties, solving the problems of difficulty in recycling nanoenzymes and secondary contamination, achieving efficient bactericidal and fruit and vegetable preservation effects.

CN119500138APending Publication Date: 2025-02-25NANTONG AIRUISI ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411626587.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing nanoenzyme bacterial agents are difficult to recover, and there are problems of secondary pollution and high treatment costs.

Method used

The Fe2O3/NiOx nanoenzyme with magnetic properties can be formed by blending and doping Fe2O3/NiOx nanoenzyme with molten salt preparation method, which can be recovered by magnetic adsorption.

Benefits of technology

It realizes efficient recycling of nanoenzymes, avoids secondary pollution, reduces treatment costs, and significantly improves the bactericidal effect and fruit and vegetable shelf life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500138A_ABST
    Figure CN119500138A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nano-enzymes and preparation thereof, and particularly relates to a preparation method and application of recoverable Fe2O3 / NiOx nano-enzymes, and the method comprises the following steps: S1, mixing a Fe < 2 + > solution and a Ni < 2 + > solution, then dissolving in absolute ethyl alcohol, uniformly mixing by ultrasonic waves, drying and grinding to obtain transition metal salt fine powder; s2, after NaNO3 is heated and melted, the transition metal salt fine powder in the step S1 is added, and oxide nanocrystals are formed after reaction; and S3, cooling, cleaning and drying the oxide nanocrystal to obtain the recoverable Fe2O3 / NiOx nano enzyme. The Fe2O3 / NiOx nano-enzyme is prepared through a molten salt preparation method and has magnetism, and the risk of secondary pollution to food can be effectively avoided through magnetic recovery while efficient sterilization and fresh keeping are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nanozymes and their preparation, and specifically relates to a recyclable Fe2O3 / NiO x Preparation method and application of nanozymes. Background Art

[0002] Food safety is an important issue that has attracted much attention. How to effectively kill bacteria and microorganisms is an important part of ensuring food safety.

[0003] As a key link in food safety, sterilization helps to inhibit the growth and reproduction of harmful microorganisms, thereby improving the safety and shelf life of food. Existing sterilization technologies include thermal sterilization, chemical sterilization, radiation sterilization, etc. Although they all have certain sterilization effects, they have many disadvantages such as poor stability, high equipment requirements, and easy to cause bacterial resistance.

[0004] In the context of challenges faced by traditional sterilization technologies, nanozyme fungicides, as an emerging technology, provide new ideas for sterilization. Nanozymes are nanomaterials with enzyme activity that have both nanoscale structure and catalytic activity. They can sterilize under mild conditions and have attracted widespread attention for their high efficiency in sterilization, environmental friendliness and biocompatibility. Nanozyme fungicides can effectively kill or inhibit the growth of microorganisms, but due to their physicochemical properties, they may have lower toxicity and environmental risks, and have the disadvantages of being difficult to recycle during use, as well as the risk of secondary pollution.

[0005] In view of the above problems, this study proposed a recyclable Fe2O3 / NiO x Nanozymes, due to their magnetic properties, can effectively avoid the risk of secondary contamination of food through magnetic recovery while effectively sterilizing. Summary of the invention

[0006] The purpose of the present invention is to provide a Fe2O3 / NiO x The preparation method of nanozyme, another purpose is to provide a recyclable Fe2O3 / NiO x Nanozymes are used to solve the problem of difficult recycling and secondary pollution in existing nano-mimetic enzyme technology.

[0007] To achieve the above purpose, the present invention realizes the co-doping of two metal elements Fe and Ni in the nanostructure by a molten salt preparation method, and forms oxide nanocrystals, and finally prepares Fe2O3 / NiO x Nanozymes are magnetic and can be recovered through magnetic adsorption, effectively avoiding the risk of secondary contamination.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] A recyclable Fe2O3 / NiO x The preparation method of nanozyme comprises the following steps:

[0010] S1, Fe 2+ Solution and Ni 2+ The solution is mixed, then dissolved in anhydrous ethanol, ultrasonically mixed, dried, and ground to obtain a transition metal salt fine powder; the Fe 2+ with Ni 2+ The molar ratio of Fe is (1~3): (1~3); 2+ Solution and Ni 2+ The volume ratio of the total volume of the mixed solution to the volume of anhydrous ethanol is 1:(10-12.5);

[0011] S2, heating and melting NaNO3, and then adding the transition metal salt powder of step S1 to form oxide nanocrystals after reaction;

[0012] S3, cooling, cleaning and drying the oxide nanocrystals to obtain recyclable Fe2O3 / NiO x Nanozymes.

[0013] It is further defined that in step S1, the ultrasonication time is 30 min to 60 min, the drying temperature is 50° C. to 70° C., and the drying time is 10 h to 12 h.

[0014] It is further defined that in step S2, during the heating and melting process of NaNO3, the heating rate is 5°C / min to 10°C / min, the temperature is 250°C to 350°C, and the reaction time is 1h to 3h.

[0015] It is further defined that in step S3, the drying temperature is 60° C. to 70° C. and the drying time is 8 h to 12 h.

[0016] It is further defined that in step S3, the cleaning is performed using an ethanol solution, and the number of cleaning times is at least 5 times, and the ethanol solution is a mixture of anhydrous ethanol and water in a volume ratio of 3:2.

[0017] Utilizing the recyclable Fe2O3 / NiO x Recyclable Fe2O3 / NiO prepared by the preparation method of nanozymes x Nanozymes.

[0018] The recyclable Fe2O3 / NiO x The structure of the nanozyme is a two-dimensional sheet structure, and the edges of the sheets are curled to form a needle-like shape.

[0019] The recyclable Fe2O3 / NiO x The bactericidal effect of nanozymes.

[0020] The recyclable Fe2O3 / NiO x Application of nanozymes in preservation of fruits and vegetables.

[0021] Therefore, the present invention adopts the above-mentioned recyclable Fe2O3 / NiO x Nanozyme and its preparation method and application, the technical effects are as follows:

[0022] 1. Recyclable Fe2O3 / NiO prepared by the present invention x Nanozymes are composite bactericidal nanomaterials with more catalytic active sites and higher activity per active site. They have obvious dual enzyme-mimicking activities of peroxidase and oxidase, and are magnetic. They can be recovered through magnetic adsorption for recycling, which not only avoids secondary pollution but also reduces treatment costs.

[0023] 2. Recyclable Fe2O3 / NiO prepared by the present invention x Nanozymes exhibit good antibacterial effects against both Gram-positive bacteria (represented by Staphylococcus aureus (S. aureus)) and Gram-negative bacteria (represented by Escherichia coli (E. coli)) and can be used for food sterilization.

[0024] 3. Recyclable Fe2O3 / NiO prepared by the present invention x Nanozymes can be used to preserve fruits and vegetables through spraying, which greatly inhibits the respiratory metabolism of fruits and vegetables, reduces the weight loss of fruits and vegetables caused by dehydration, and helps to further extend the shelf life of fruits and vegetables. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 a is recyclable Fe2O3 / NiO x a) Scanning electron microscopy image of nanozyme; b) Transmission electron microscopy image; c) Transmission electron microscopy elemental analysis image;

[0026] Figure 2 Recyclable Fe2O3 / NiO x TMB (3,3',5,5'-tetramethylbenzidine) color image of nanozyme;

[0027] Figure 3 Recyclable Fe2O3 / NiO x Nanozyme power curve diagram;

[0028] Figure 4 Recyclable Fe2O3 / NiO x The effect of nanozyme sterilization on bacterial plate coating;

[0029] Figure 5 Recyclable Fe2O3 / NiOx Bactericidal effect of nanozymes, a is recyclable Fe2O3 / NiO x The relationship between the bactericidal effect of nanozymes and time; b is the recyclable Fe2O3 / NiO x The relationship between the bactericidal effect and concentration of nanozymes;

[0030] Figure 6 Recyclable Fe2O3 / NiO x Nanozyme preservation effect; a is recyclable Fe2O3 / NiO x Schematic diagram of the appearance changes of bananas after being treated with nanozymes during storage; b is a diagram showing the changes in the respiration intensity of bananas over time after being treated with different materials; c is a diagram showing the changes in the weight loss rate of bananas over time after being treated with different materials;

[0031] Figure 7 Recyclable Fe2O3NiO x Nanozyme magnet recycling effect diagram. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0033] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0034] Technologies, methods, and equipment known to ordinary technicians in the relevant field may not be discussed in detail, but where appropriate, the technologies, methods, and equipment should be considered as part of the specification.

[0035] In addition, it should be understood that although this specification is described according to the implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. These other implementation modes are also covered within the protection scope of the present invention.

[0036] The present invention provides a recyclable Fe2O3 / NiO x The preparation method of nanozyme comprises the following steps:

[0037] S1, Fe 2+ Solution and Ni 2+ The solutions are mixed, then dissolved in anhydrous ethanol, ultrasonically mixed, dried, and ground to obtain fine powder of transition metal salt;.

[0038] In the present invention, Fe 2+ with Ni 2+The molar ratio is (1~3):(1~3).

[0039] Preferably, Fe 2+ with Ni 2+ The molar ratio is 1:1, 1:2, 1:3, 2:1, 2:3, 3:1 or 3:2.

[0040] Preferably, Fe 2+ The solution is FeCl2 solution, Ni 2+ The solution is NiCl2 solution.

[0041] In the present invention, Fe 2+ Solution and Ni 2+ The volume ratio of the total volume of the mixed solutions to the volume of anhydrous ethanol is 1:(10-12.5).

[0042] Preferably, the volume ratio is 1:10, 1:11, 1:12, 1:12.5.

[0043] In step S1, the ultrasonication time is 30 min to 60 min, the drying temperature is 50° C. to 70° C., and the drying time is 10 h to 12 h.

[0044] Preferably, the ultrasonication time is 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min; the drying temperature is 50°C, 55°C, 60°C, 65°C or 70°C; and the drying time is 10 h, 11 h or 12 h.

[0045] S2, heating and melting NaNO3, and then adding the transition metal salt powder of step S1 to form oxide nanocrystals after reaction;

[0046] In step S2 of the present invention, during the heating and melting process of NaNO3, the heating rate is 5°C / min to 10°C / min, the temperature is 250°C to 350°C, and the reaction time is 1h to 3h.

[0047] Preferably, the heating rate is 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min; the temperature is 250°C, 280°C, 300°C, 320°C, 330°C or 350°C; and the reaction time is 1h, 1.5h, 2h, 2.5h or 3h.

[0048] S3, cooling, cleaning and drying the oxide nanocrystals to obtain recyclable Fe2O3 / NiO x Nanozymes.

[0049] In step S3 of the present invention, the drying temperature is 60° C. to 70° C. and the drying time is 8 h to 10 h.

[0050] Preferably, the drying temperature is 60° C., 65° C. or 70° C., and the drying time is 8 h, 8.5 h, 9 h, 9.5 h or 10 h.

[0051] In step S3 of the present invention, the cleaning is performed using an ethanol solution, and the number of cleaning times is at least 5 times. The ethanol solution is a mixture of anhydrous ethanol and water in a volume ratio of 3:2.

[0052] The present invention utilizes the above-mentioned recyclable Fe2O 3 / NiO x Recyclable Fe2O3 / NiO prepared by the preparation method of nanozymes x Nanozymes have a two-dimensional sheet structure, and the edges of the sheets curl to form a needle-like shape, which has a significant effect in sterilization. They are also magnetic and easy to recycle.

[0053] The following is a detailed explanation of the processing and performance of the catalyst of the present invention with reference to several groups of specific examples.

[0054] It should be noted that the operations used in the following examples are all conventional operations in the art unless otherwise specified. The pharmaceutical reagents used in the following examples are all purchased from the market.

[0055] Example 1

[0056] The recyclable Fe2O3 / NiO provided in this embodiment x The preparation method of nanozyme comprises the following steps:

[0057] S1. Take 20 mL of 1 mol / L FeCl2 and NiCl2 hydrate solutions, that is, mix FeCl2 and NiCl2 in a molar ratio of 1:1 and dissolve them in 500 mL of anhydrous ethanol. Treat with ultrasound for 30 min to achieve atomic-level uniform mixing.

[0058] S2. Place the solution after ultrasonic treatment in an oven and dry it at 70° C. for 12 h. Grind the dried solid into a fine powder of transition metal salt with an average particle size of 5 μm.

[0059] S3. Use a crucible as a reaction container, heat NaNO3 to 300°C in a muffle furnace to melt, control the heating rate at 5°C / min, then quickly add transition metal salt fine powder into the molten NaNO3, maintain the reaction time for 2h, and form oxide nanocrystals.

[0060] S4. After the reaction is completed, the product is quickly transferred to cold water for cooling, and then centrifuged and washed with a mixture of anhydrous ethanol and water in a volume ratio of 3:2. The operation is repeated 5 times, and finally dried at 60 ° C for 8 h to obtain recyclable Fe2O3 / NiO x Nanozymes.

[0061] Example 2

[0062] The recyclable Fe2O3 / NiO provided in this embodiment x The preparation method of nanozyme comprises the following steps:

[0063] S1. Take 10 mL of 0.5 mol / L FeCl2 hydrate solution and 10 mL of 0.75 mol / L NiCl2 hydrate solution, i.e., mix FeCl2 and NiCl2 in a molar ratio of 2:3, dissolve in 300 mL of anhydrous ethanol, and treat with ultrasound for 45 min.

[0064] S2. Place the solution after ultrasonic treatment in an oven and dry it at 60° C. for 10 h. Grind the dried solid into a fine powder of transition metal salt with an average particle size of 5 μm.

[0065] S3. Use a crucible as a reaction container, heat NaNO3 to 330°C in a muffle furnace to melt, control the heating rate at 8°C / min, then quickly add transition metal salt fine powder into the molten NaNO3, maintain the reaction time for 2.5 hours, and form oxide nanocrystals.

[0066] S4. After the reaction is completed, the product is quickly transferred to cold water for cooling, and then centrifuged and washed with a mixture of anhydrous ethanol and water in a volume ratio of 3:2. The operation is repeated 5 times, and finally dried at 60 ° C for 8 h to obtain recyclable Fe2O3 / NiO x Nanozymes.

[0067] Example 3

[0068] The recyclable Fe2O3 / NiO provided in this embodiment x The preparation method of nanozyme comprises the following steps:

[0069] S1. Take 25 mL of 1.5 mol / L FeCl2 solution and 15 mL of 0.75 mol / L NiCl2 solution, that is, mix FeCl2 and NiCl2 in a molar ratio of 3:1, dissolve in 400 mL of anhydrous ethanol, and treat with ultrasound for 60 min.

[0070] S2. The solution after ultrasonic treatment is placed in an oven and dried at 60° C. for 12 h. The dried solid is fully ground into a transition metal salt fine powder with an average particle size of 5 μm.

[0071] S3. Use a crucible as a reaction container, heat NaNO3 to 350°C in a muffle furnace to melt, control the heating rate at 10°C / min, then quickly add transition metal salt fine powder into the molten NaNO3, maintain the reaction time for 1.0h, and form oxide nanocrystals.

[0072] S4. After the reaction is completed, the product is quickly moved to cold water for cooling, and then centrifuged and washed with a mixture of anhydrous ethanol and water in a volume ratio of 3:2. The operation is repeated 5 times, the drying temperature is 65 ° C, the drying time is 10 h, and the recyclable Fe2O3 / NiO is obtained. x Nanozymes.

[0073] Example 4

[0074] The recyclable Fe2O3 / NiO provided in this embodiment x The preparation method of nanozyme comprises the following steps:

[0075] S1. Take 15 mL of 1 mol / L FeCl2 and NiCl2 hydrate solutions, i.e., mix FeCl2 and NiCl2 in a molar ratio of 1:1, dissolve in 350 mL of anhydrous ethanol, and treat with ultrasound for 30 min.

[0076] S2. Place the solution after ultrasonic treatment in an oven and dry it at 70° C. for 12 h. Grind the dried solid into a fine powder of transition metal salt with an average particle size of 5 μm.

[0077] S3. Use a crucible as a reaction container, heat NaNO3 to 300°C in a muffle furnace to melt, control the heating rate at 6°C / min, then quickly add transition metal salt fine powder into the molten NaNO3, maintain the reaction time for 3h, and form oxide nanocrystals.

[0078] S4. After the reaction is completed, the product is quickly moved to cold water for cooling, and then centrifuged and washed with a mixture of anhydrous ethanol and water in a volume ratio of 3:2. The operation is repeated 5 times, the drying temperature is 60 ° C, and the drying time is set to 7 h to obtain recyclable Fe2O3 / NiO x Nanozymes.

[0079] The prepared Fe2O3 / NiO x The performance of nanozymes was verified.

[0080] During verification, the Fe2O3 / NiO obtained in Example 1 x Taking nanozyme as an example, its performance was tested.

[0081] Test 1

[0082] See also Figure 1 , Figure 1 a is Fe2O3 / NiO x Scanning electron microscopy image of the nanozyme, illustrating the synthesized Fe2O3 / NiO x Nanozymes appear as two-dimensional sheet structures, with some of the sheets curled at the edges to form a unique needle-like morphology. Figure 1The TEM image in b shows that the material is a two-dimensional thin layer material, in which lattice fringes can be clearly observed on the curled flakes, indicating that the material has a high degree of crystallinity. Figure 1 c is the result of further studying the element composition and distribution of the composite material using transmission electron microscopy. It can be seen that Fe, Ni, and O elements are evenly distributed in Fe2O3 / NiO x In nanozymes, this indicates that Fe and Ni are evenly distributed in the form of oxide nanocrystals, which helps to improve the catalytic performance of the material.

[0083] Test 2

[0084] Fe2O3 nanosheets prepared by the same method as in Example 1 using FeCl2 hydrate as raw material alone; NiO x Nanosheets; then with Fe2O3 / NiO x for comparison.

[0085] The Fe2O3 / NiO in Example 1 was chromogenically treated by catalytic oxidation of TMB (3,3',5,5'-tetramethylbenzidine). x The enzyme-like activity of Fe2O3 nanosheets and NiO x Nanosheets are used for comparison. Under the action of a single material, the darker the TMB color, the higher the oxidase activity of the material; under the combined action of the material and H2O2, the darker the TMB color, the higher the peroxidase activity of the material.

[0086] See the color results for Figure 2 Whether or not H2O2 is added, it is Fe2O3 / NiO x The color of the group is darker, which shows that Fe2O3 / NiO x It has stronger dual enzyme-mimicking activities of oxidase and peroxidase.

[0087] In order to further study the Fe2O3 / NiO x The affinity and catalytic activity of the nanozymes for substrates were investigated using enzyme kinetics.

[0088] The test method is: the above-mentioned Fe2O3 nanosheets, NiO x Nanosheets, Fe2O3 / NiO x The three samples were mixed with ultrapure water at a ratio of 1:20 to obtain Fe2O3 solution, NiOx solution and Fe2O3 / NiOx solution. xSolution. Enzyme kinetics analysis was performed using H2O2 and TMB (3,3',5,5'-tetramethylbenzidine) as substrates. When H2O2 was used as substrate, 10 μL of the material was added to 200 μL of HAc-NaAc buffer solution (pH 4.5), and finally 10 μL of TMB was added and mixed. The TMB concentration was fixed at 10 mmol / L. The H2O2 concentration was changed (0.0875-1.4 mol / L), and the absorbance (A) at 652 nm before and after the reaction was measured. 652 Similarly, when TMB was used as the substrate, 10 μL of the material was added to 200 μL of HAc-NaAc buffer solution (pH 4.5), 50 μL of H2O2 was added, and finally 10 μL of TMB was added and mixed. The H2O2 concentration was fixed at 0.35 mol / L, and the TMB concentration (1.25-20 mmol / L) was changed for measurement.

[0089] Enzyme kinetics curves see Figure 3 It can be seen that whether H2O2 is added or not, Fe2O3 / NiO x They have good affinity and catalytic activity for substrates.

[0090] Test 3

[0091] The Fe2O3 / NiO in the above Example 1 was tested by flat plate coating method. x The fewer the number of colonies on the plate, the better the bactericidal effect of the material.

[0092] The test method is: the above-mentioned Fe2O3 nanosheets, NiO x Nanosheets, Fe2O3 / NiO x The three samples were mixed with ultrapure water at a ratio of 1:20 to obtain Fe2O3 solution, NiO x Solution and Fe2O3 / NiO x 50 μL of material solution and 50 μL of 10 7 The CFU / mL bacterial solution was mixed and incubated for 30 minutes and then spread on the LB agar plate. After spreading, the plate was placed in a 37°C incubator for 24 hours and then the colonies were counted to clarify the bactericidal performance of the nanozyme.

[0093] See also Figure 4 , according to the bactericidal effect on Staphylococcus aureus and Escherichia coli, Fe2O3 / NiO x The bactericidal effect of Fe2O3 / NiO x It has good broad-spectrum bactericidal properties.

[0094] Test 4

[0095] The method of calculating the sterilization rate was used to calculate the sterilization rate of Fe2O3 / NiO in Example 1. x Further evaluate the relationship between the bactericidal effect and time and material concentration.

[0096] The test method is: the above-mentioned Fe2O3 nanosheets, NiO x Nanosheets, Fe2O3 / NiO x The three samples were mixed with ultrapure water in a certain proportion to obtain Fe2O3 solution, NiO x Solution and Fe2O3 / NiO x 100 μL of different concentrations of materials (10-60 μg / mL) were mixed with bacterial solution (10 7 CFU / mL, 100 μL) were mixed and cultured in a constant temperature shaker at 37°C and 200 rpm. The optical density (OD) at 600 nm was monitored by a UV-visible spectrophotometer. 600 ), and then evaluate the bactericidal effect according to the bactericidal rate calculation formula.

[0097] See also Figure 5 a, Time-dependent sterilization curve clearly shows that Fe2O3 / NiO x Compared with Fe2O3 and NiO x It can achieve efficient sterilization in a shorter time and can completely kill Escherichia coli and Staphylococcus aureus within 30 minutes, with considerable sterilization effect; see Figure 5 b. From the concentration-dependent sterilization curve, it can be found that with the increase of concentration, Fe2O3 / NiO x The above test results show that Fe2O3 / NiO x Nanozymes have excellent bactericidal effects.

[0098] Test 5

[0099] Banana was selected as a representative fruit to verify the Fe2O3 / NiO x The application effect of nanozymes as spray coatings in the preservation of fruits and vegetables.

[0100] The test method is: the above-mentioned Fe2O3 nanosheets, NiO x Nanosheets, Fe2O3 / NiO x The three samples were mixed with ultrapure water at a ratio of 1:20 to obtain Fe2O3 solution, NiO x Solution and Fe2O3 / NiO xThe solution was sprayed evenly on the surface of the bananas. After the surface of the bananas dried naturally, all treatment groups were stored at room temperature. Each group of bananas was photographed and weighed regularly, the fruit weight loss rate was calculated, and the changes in respiration intensity were measured. The results are shown in Figure 6 .

[0101] See also Figure 6 a. From the perspective of the preservation effect on bananas, the other treatment groups began to show browning to varying degrees on the third day, while Fe2O3 / NiO x The group still had a good appearance until the 12th day, indicating that the Fe2O3 / NiO x It showed better preservation effect than other treatment groups; see Figure 6 b, Banana is a representative of respiratory climacteric fruits. Its respiratory intensity first increased and then decreased during storage. The control group reached its respiratory peak on the 6th day. x The respiratory peak of the group was significantly delayed and the overall respiratory intensity was lower, indicating that the film formed by spraying the material on the surface of the banana can effectively inhibit the entry and exit of gas, thereby inhibiting respiration and reducing respiratory metabolism; see Figure 6 c, Spraying materials limited the dehydration of bananas (assessed by weight loss), Fe2O3 / NiO x The above test results show that Fe2O3 / NiO x Nanozymes have a preservative effect on fruits and vegetables.

[0102] Test 6

[0103] The Fe2O3 / NiO in Example 1 was studied by magnet adsorption experiment x recyclability.

[0104] See also Figure 7 , verifying the feasibility of magnetic recovery of materials and providing a scientific basis for their recycling and environmental friendliness.

[0105] The above test was conducted using the Fe2O3 / NiO x When the Fe2O3 / NiO x The samples were verified to have the same Fe2O3 / NiO x It has similar properties, dual enzyme-mimicking activity, good affinity and catalytic activity for substrates, and antibacterial properties. It also has application potential in the preservation of fruits and vegetables.

[0106] The present invention realizes the co-doping of two metal elements, Fe and Ni, in the nanostructure through a simple molten salt preparation method, and realizes the uniform distribution of the two metal elements in the nanostructure by controlling the synthesis conditions within a specific range to achieve a synergistic effect. x Nanozymes have dual enzyme-mimicking activities of oxidase and peroxidase, and can efficiently sterilize Gram-positive bacteria (Staphylococcus aureus) and Gram-negative bacteria (Escherichia coli) by catalyzing the production of oxygen-containing free radicals. At the same time, it has shown a good application effect in the preservation of fruits and vegetables, greatly inhibiting the respiratory metabolism of fruits and vegetables, reducing the weight loss rate caused by dehydration, and helping to further extend the shelf life of fruits and vegetables. In addition, since the nanozyme is made based on two magnetic elements, Fe and Ni, it can be separated and recovered by simple magnetic adsorption after completing the catalytic sterilization process in the system, thereby being reused, avoiding secondary pollution to the food system.

[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A recyclable Fe2O3 / NiO x The method for preparing nanozyme is characterized in that: The following steps are involved: S1, Fe 2+ Solution and Ni 2+ The solution is mixed, then dissolved in anhydrous ethanol, ultrasonically mixed, dried, and ground to obtain a transition metal salt fine powder; the Fe 2+ with Ni 2+ The molar ratio of Fe is (1~3): (1~3); 2+ Solution and Ni 2+ The volume ratio of the total volume of the mixed solution to the volume of anhydrous ethanol is 1:(10-12.5); S2, heating and melting NaNO3, and then adding the transition metal salt powder of step S1 to form oxide nanocrystals after reaction; S3, cooling, cleaning and drying the oxide nanocrystals to obtain recyclable Fe2O3 / NiO x Nanozymes.

2. The recyclable Fe2O3 / NiO according to claim 1 x The method for preparing nanozyme is characterized in that: In the step S1, the ultrasonication time is 30 min to 60 min, the drying temperature is 50° C. to 70° C., and the drying time is 10 h to 12 h.

3. The recyclable Fe2O3 / NiO according to claim 1 x The method for preparing nanozyme is characterized in that: In the step S2, during the heating and melting process of NaNO3, the heating rate is 5°C / min to 10°C / min, the temperature is 250°C to 350°C, and the reaction time is 1h to 3h.

4. The recyclable Fe2O3 / NiO according to claim 1 x The method for preparing nanozyme is characterized in that: In step S3, the drying temperature is 60° C. to 70° C., and the drying time is 8 h to 12 h.

5. The recyclable Fe2O3 / NiO according to claim 1 x The method for preparing nanozyme is characterized in that: In step S3, the cleaning is performed using an ethanol solution, and the number of cleaning times is at least 5 times. The ethanol solution is a mixture of anhydrous ethanol and water in a volume ratio of 3:

2.

6. Utilizing the recyclable Fe2O3 / NiO according to claim 1 x Recyclable Fe2O3 / NiO prepared by the preparation method of nanozymes x Nanozymes.

7. The recyclable Fe2O3 / NiO according to claim 6 x Nanozyme, characterized in that The recyclable Fe2O3 / NiO x The structure of the nanozyme is a two-dimensional sheet structure, and the edges of the sheets are curled to form a needle-like shape.

8. The recyclable Fe2O3 / NiO as claimed in claim 6 x The bactericidal effect of nanozymes.

9. The recyclable Fe2O3 / NiO as claimed in claim 6 x The effect of nanozymes in preserving fruits and vegetables.